Respuestas

2013-07-10T17:18:06+02:00
Dahiaaan,
En los dos casos, el area sombreada será igual:
             As = At - Ans
              As = area sombreada
              At - area total
              Ans = area no sombreada

Asi:
1) At = y^2
   Ans= 2x^2
                       As = y^2 - 2x^2

2)     At = x^2
     a) As = x^2 - 3/4x^2
              = 1/4x^2
   
 b) As = x^2 - 7/8x2
              = 1/8x^2
     c) As = x^2 - 8/9x^2
              = 1/9x^2
     d) As = x^2 - 5/9x^2
              = 4/x^2